A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 38 PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Septi Emi Mutia; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the second year students of SMPN 38 Pekanbaru in comprehending recount texts. The research data were collected from March to April 2017. The subject of this research was class VIII-1 which consisted of 30 students. The data were collected by administering a test to the students in the form of multiple choice test. Based on the data analysis it was found out that the highest score obtained by the students was in finding social function with the mean score of 78.66 which categorized into good level, and the lowest score was in finding meaning of vocabulary with the mean score of 50.33 which categorized into mediocre level. As a conclusion, the ability of the second year students in reading comprehension was in the good level with the mean score of 65.3. The implication of the finding is that the students should increase their comprehension in order to reach excellent level.Keywords: Reading Ability, Comprehending Recount Texts.